Pengembangan Instrumen Five-Tier Diagnostic Test untuk Mengidentifikasi Miskonsepsi pada Materi Gerak Lurus - Amalia Nur Rizqiah; Titin Sunarti (Pendidikan Fisika Universitas Nurul Huda, 2025)
Misconceptions about the concept of straight motion are still widely found in physics learning and can hinder students' overall understanding. This research aims to develop a five-tier diagnostic test instrument to identify student misconceptions more deeply. The method of this research is development research (R&D) with the ADDIE (Analyze, Design, Development, Implementation and Evaluation) model. The instrument was validated by experts with a feasibility result of 91% and empirically tested with a reliability of 0.756. The instrument was then applied to 35 high school grade XI students. The results showed that 8% of students scientific conception, 9% almost scientific conception, 31% lack of knowledge (LK), 44% misconception (MSC) and 8% not understand (NU). Students' misconceptions were dominated by the concept of average speed and acceleration with the largest causative factor being preconception of 33%. This study recommends that follow-up studies not only identify misconceptions and causes from students but also need to identify causes as a basis for designing appropriate learning strategies